Northern Benguela Merluccius paradoxus Annual Growth From Otolith Chronologies Used for Age Verification and as Indicators of Fisheries-Induced and Environmental Changes - Wilhelm, Margit R.; Black, Bryan A.; Lamont, Tarron; Paulus, Sarah C.; Bartholomae, Chris; Louw, Deon C. (Frontiers in Marine Science, 2020)
In this study we develop a 32-year (1982–2013) otolith biochronology of the commercially important deepwater hake Merluccius paradoxus in the northern Benguela, Namibia. Mean annual growth (mm) calculated from 140 thin-sectioned M. paradoxus otoliths were compared with change in mean length at age 3 to age 4 determined from Namibian whole-otolith-read age-length keys (ALKs). Annual growth rates calculated from the two methods (overlapping 2000–2013) were strongly positively correlated (ρ = 0.730, n = 14, p < 0.01). This indirectly validated annual age determination of M. paradoxus, the accuracy of otolith chronologies, and the ability of ALKs to capture annual variability in fish growth. Annual M. paradoxus growth rates were significantly positively correlated with the July–September upwelling index 1982–2013 at 30°S, (ρ = 0.414, n = 32, p < 0.05) and positively correlated with August mean chlorophyll-a concentrations (as indicator for primary production) 2002–2013 in the 28–30°S area (ρ = 0.734, n = 12, p < 0.01). Annual M. paradoxus growth rates significantly negatively correlated with October (austral spring) sea surface temperatures in the 24–28°S area (ρ = −0.381, n = 32, p < 0.05). This Orange-River Namaqua upwelling cell corresponds to the area where juvenile and young adult M. paradoxus live, suggesting growth rate strongly responds to local forcing. We also determined that mean length-at-age 3 calculated from ALKs (current and literature) significantly increased from 1977 through 2016 at 0.075 cm.year–1 (t = 3.04, df = 41, p = 0.004), while length-at-age 8 significantly decreased at 0.25 cm.year–1 (t = −3.59, df = 30, p = 0.001). Both trends may indicate fisheries-induced adaptive changes. M. paradoxus occurring at >300 m bottom depth, are thus strongly influenced by fisheries. As an upper-level demersal predator, this species integrates signals throughout the food web to provide a unique “view from the top” of long-term changes in the northern Benguela upwelling system. These results provide background ranges of growth variability and context for what will likely be negative impacts of predicted decreases in future upwelling.